Rudolf Carnap, Tagebücher. Band 2. 1920-1935: Herausgegeben von Christian Damböck, unter Mitarbeit von Brigitta Arden, Roman Jordan, Brigitte Parakenings und Lois M. Rendl - Carnap, Rudolf (2022)
Rudolf Carnap (1891-1970) was among the most important representatives of interwar European philosophy as well as of postwar American analytic philosophy. His early diaries, with whom the edition of his writings from the estate is opened, offer unique insights into the motives and thoughts of a key figure of twentieth-century philosophy and provide indispensable information on the genesis and background of Carnap's work, but also on the (pre)history of the Vienna Circle and Logical Empiricism. Volume 1: https://e-book.fwf.ac.at/o:1697 Volume 2: https://e-book.fwf.ac.at/o:1707